The Effect Of Face Print Attendance On Employee Performance At The Food Security And Agriculture Service Samosir Regency - Marganda P. Sitanggang; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the effect of Face Print Attendance on Employee Performance at the Samosir Regency Food Security and Agriculture Office. This research was carried out at the Samosir Regency Food Security and Agriculture Office. The type of research is quantitative associative. The sample in this study is 96 employees with ASN and honorary status at the Samosir Regency Food Security and Agriculture Office. The sampling technique in this study used the entire population of 64 people. The results of the study show that Face Print Attendance has a significant influence on Employee Performance as shown by a T-Statistic value of 3.549 > a t table of 1.669 and a P Value of 0.001 < 0.05. This shows that improvements in Face Print Attendance can improve Employee Performance at the Samosir Regency Food Security and Agriculture Office.